Teaching Environment Management at Dharma Wanita Kindergarten in Cangkringsari Village: Pengelolaan Lingkungan Pembelajaran Di TK Dharma Wanita Desa Cangkringsari - Nisak, Nur Maslikhatun; Noviansyah, Hisyam Amir; Astaningrum, Risma Yuwanita; Hakim, Mohammad Rijal; Faramida, Shafa Ayu; Muhammad, Fajar (Procedia of Social Sciences and Humanities, 2022)
This study aims to determine the layout design management of the indoor and outdoor PAUD and TK environment in Cangkringsari Village. This type of research is a qualitative study using interview and observation techniques on the subjects of the Dharma Wanita Kindergarten Principal. The results show that Dharma Wanita Kindergarten attempts to create (1) a comfortable psychological environment for children, and (2) a physical environment where the principles of harmony, beauty, balance, artistic order, safety, economy and unity are prioritized in environmental management.